2000
DOI: 10.1038/35006676
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Sm-like proteins function in mRNA decapping and decay

Abstract: One of the main mechanisms of messenger RNA degradation in eukaryotes occurs by deadenylation-dependent decapping which leads to 5'-to-3' decay. A family of Sm-like (Lsm) proteins has been identified, members of which contain the 'Sm' sequence motif, form a complex with U6 small nuclear RNA and are required for pre-mRNA splicing. Here we show that mutations in seven yeast Lsm proteins (Lsm1-Lsm7) also lead to inhibition of mRNA decapping. In addition, the Lsm1-Lsm7 proteins co-immunoprecipitate with the mRNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
454
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 394 publications
(485 citation statements)
references
References 22 publications
(31 reference statements)
26
454
1
4
Order By: Relevance
“…To assess the RNA dependence of proteinprotein interactions, lysates were treated with RNAseA at 0.5 μg μl −1 for 20 min at room temperature before immunoprecipitation procedures as described in ref. 18.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…To assess the RNA dependence of proteinprotein interactions, lysates were treated with RNAseA at 0.5 μg μl −1 for 20 min at room temperature before immunoprecipitation procedures as described in ref. 18.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…These results were almost identical to those obtained in K. lactis and confirmed that the lack of the C-terminal region of the protein severely affects cell viability during the stationary phase. In S. cerevisiae, the role of Lsm4p has been associated with mRNA splicing and decapping (Bouveret et al, 2000;Mayes et al, 1999;Thaurun et al, 2000) and work is in progress to verify whether these processes are altered in the K. lactis and S. cerevisiae strains expressing the truncated form of KlLsm4p. Cells were grown on YPD medium and OD 600 was measured at the indicated times.…”
Section: Complementation Of S Cerevisiaementioning
confidence: 99%
“…The process and regulation of mRNA turnover is a fundamental aspect of gene expression+ A major pathway of mRNA turnover for both stable and unstable transcripts has been identified in Saccharomyces cerevisiae+ In this pathway, degradation is initiated by deadenylation of the 39 poly(A) tail (Muhlrad & Parker, 1992;Decker & Parker, 1993)+ In yeast, deadenylation is followed by removal of the 59 m7 GpppN cap structure, and exonucleolytic digestion in a 59-39 direction (Decker & Parker, 1993;Hsu & Stevens, 1993;Beelman et al+, 1996)+ Poly(A) shortening requires two proteins, Ccr4p and Pop2p, which have recently been shown to be components of the yeast deadenylase )+ Following deadenylation, the Dcp1p/Dcp2p decapping complex decaps mRNAs at their 59 end Dunckley & Parker 1999)+ Although Dcp1p and Dcp2p are the only proteins known to be required for decapping (Dunckley & Parker, 1999, the rate of decapping is affected by several trans-acting factors+ These accessory factors include Pat1p/Mrt1p, the Lsm complex (consisting of Lsm1p-Lsm7p), Vps16p, Edc1p, and Edc2p Zhang et al+, 1999;Bonnerot et al+, 2000;Tharun et al+, 2000;Wyers et al+, 2000;Dunckley et al+, 2001)+ Pat1p/Mrt1p was originally identified as a genetic lesion that slows mRNA decapping, and was later shown to also be required for efficient translational initiation Wyers et al+, 2000)+ There are nine Lsm proteins in yeast, which form two distinct seven-member ring structures of differing function (Salgado-Garrido et al+, 1999)+ Lsm2p-Lsm8p associate in the nucleus and are involved in U6 snRNA metabolism, whereas Lsm1p-Lsm7p associate in the cytoplasm and affect decapping of mRNAs (Mayes et al+, 1999;Bouveret et al+, 2000;Tharun et al+, 2000)+ Vps16p was identified as a mutant that affected decapping rates in vitro, and Edc1p and Edc2p have been shown to be in a complex with Dcp1p and Dcp2p (Zhang et al+, 1999;Dunckley et al+, 2001)+ Although the mechanism of how these proteins en-hance decapping is unclear, it is possible a class of decapping enhancers may do so by directly affecting the translatability of the mRNA+ Indeed, translational repression may be a first step required for efficient decapping, as recent studies have shown the cap-binding protein, eIF-4E, can inhibit decapping activity both in vivo and in vitro (Schwartz & Parker, 1999+ Given this, a critical issue to resolve in understanding mRNA decay is to determine the nature of transitions between translating and nontranslating states of mRNAs+…”
Section: Introductionmentioning
confidence: 99%